Trends in prevalence, health disparities, and early detection of dementia: A 10-year nationally representative serial cross-sectional and cohort study - Lu, Kevin; Xiong, Xiaomo; Li, Minghui; Yuan, Jing; Luo, Ye; Friedman, Daniela B. (Frontiers in Public Health, 2023)
Objective: To identify the trends in the prevalence of mild cognitive impairment (MCI) and dementia, and to determine risk factors associated with the early detection of dementia among U.S. middle-aged and older adults. Methods: We used a 10-year nationally representative longitudinal data from Health and Retirement Study (HRS) (2006-2016). Adults aged 55 years or older were included to examine the trend. To identify the associated factors, adults aged 55 years or older in 2006 who developed MCI or dementia in subsequent waves until the 2016 wave were included. Early and late detection of dementia were identified using the Langa-Weir classification of cognitive function. Multivariate logistic regression models were used to identify factors associated with the early detection of dementia. Results: The sample size for the analysis of the prevalence of MCI and dementia ranged from 14,935 to 16,115 in the six survey years, and 3,729 individuals were identified out to determine associated factors of the early detection of dementia. Among them, participants aged 65 years or older accounted for 77.9%, and the male participants accounted for 37.2%. The 10-year prevalence of MCI and dementia was 14.5% and 6.6%, respectively. We also found decreasing prevalence trends in MCI (from 14.9% to 13.6%) and dementia (from 7.4% to 6.0%) overall in the past decade. Using logistic regression controlling for the year, non-Hispanic black (MCI: OR=2.83, P<0.001; dementia: OR=2.53, P<0.001) and Hispanic (MCI: OR=2.52, P<0.001; dementia: OR=2.62, P<0.001) had a higher prevalence of both MCI and dementia than non-Hispanic white participants. In addition, men had a lower prevalence of MCI (OR=0.94, P=0.035) and dementia (OR=0.84, P<0.001) compared to women. Associated factors of the early detection of dementia include age, gender, race, educational attainment, stroke, arthritis diseases, heart problems and, pensions. Conclusion: This study found a decreasing trend in the prevalence of MCI and dementia in the past decade, and associated racial/ethnic and gender disparities among U.S. middle-aged and older adults. Healthcare policies and strategies may be needed to address health disparities in the prevalence and take the associated factors of the early detection of dementia into account in clinical settings.